2019
DOI: 10.1016/j.molmet.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Repeated cold exposures protect a mouse model of Alzheimer's disease against cold-induced tau phosphorylation

Abstract: Objective Old age is associated with a rise in the incidence of Alzheimer's disease (AD) but also with thermoregulatory deficits. Indicative of a link between the two, hypothermia induces tau hyperphosphorylation. The 3xTg-AD mouse model not only develops tau and amyloid pathologies in the brain but also metabolic and thermoregulatory deficits. Brown adipose tissue (BAT) is the main thermogenic driver in mammals, and its stimulation counteracts metabolic deficits in rodents and humans. We thus inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 61 publications
(136 reference statements)
0
17
0
Order By: Relevance
“…Since tau phosphorylation has been repeatedly shown to follow body temperature modulation (Arendt et al, 2003;Planel et al, 2007;Stieler et al, 2011), we could have expected a protective effect of β3AR stimulation. For example, we recently showed that improved BAT thermogenesis through repeated cold exposure protects old 3xTg-AD mice from cold-induced tau phosphorylation (Tournissac et al, 2019). However, the present study design did not fully explore the hypothesis that β3AR stimulation impacts tau phosphorylation, because the animals were kept at room temperature and not exposed to any frank thermoregulatory challenge (i.e.…”
Section: β3ar Stimulation Decreases Insoluble Aβ42/aβ40 Ratio But Hasmentioning
confidence: 87%
See 3 more Smart Citations
“…Since tau phosphorylation has been repeatedly shown to follow body temperature modulation (Arendt et al, 2003;Planel et al, 2007;Stieler et al, 2011), we could have expected a protective effect of β3AR stimulation. For example, we recently showed that improved BAT thermogenesis through repeated cold exposure protects old 3xTg-AD mice from cold-induced tau phosphorylation (Tournissac et al, 2019). However, the present study design did not fully explore the hypothesis that β3AR stimulation impacts tau phosphorylation, because the animals were kept at room temperature and not exposed to any frank thermoregulatory challenge (i.e.…”
Section: β3ar Stimulation Decreases Insoluble Aβ42/aβ40 Ratio But Hasmentioning
confidence: 87%
“…The present study aimed at investigating whether β3AR agonist administration induces BAT thermogenesis and exerts an effect on cognitive behavior and AD neuropathology in a mouse model of the disease. The 3xTg-AD mice was selected to test the effect of β3AR stimulation in AD because this model displays age-dependent metabolic and thermoregulatory deficits and was shown to respond to thermoneutrality and BAT stimulation induced by repeated cold exposure (Knight et al, 2013;Tournissac et al, 2019;Vandal et al, 2016). This led to the hypothesis that pharmacological BAT stimulation could exert benefit on AD-like behavior and neuropathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermoregulatory deficits coincide with a rise in the incidence of metabolic syndrome and a set of neurodegenerative disorders in old age [103]. A previous study indicated that thermogenesis stimulation improved metabolic deficits and protected a mouse model of AD [104]. Increasing evidence has suggested that adipose tissue influences brain development, cognition, and the risk for neurodegenerative disorders throughout one’s lifespan [105].…”
Section: Discussionmentioning
confidence: 99%